EFEKTIVITAS STRATEGI PROMOSI MELALUI PROMOTION MIX SEBAGAI UPAYA PENGUATAN EKSISTENSI LEMBAGA STAIN KEDIRI - Siti Amanah (Mediakita, 2018)
The research aimed : (1).to describe the form of promotional strategies that have been applied by IAIN Kediri in order to strengthen the existence of institutions to increase the interest and number of new students at IAIN Kediri; (2). to analyze the effectiveness of the implementation of promotional strategies through promotion mix and its benefits in supporting the strengthening of the existence of IAIN Kediri institutions. This study was categoried as descriptive research type with qualitative method. The methods of collecting data used were direct observation, participative, in depth interview and documentation. To determine the subjects of this reseach, the writer used purposive sampling. The writer used Miles and Huberman’s interactive data analysis which consisted of data reduction, data display, conclusion, and verification The result showed that: (1). Promotional strategies that have been applied by IAIN Kediri in order to strengthen the existence of institutions to increase interest and the number of new students at IAIN Kediri through the distribution of brochures, pamphlets, banners, baliho, advertising in print media and electronic media and online media. The use of media in promotional strategies at IAIN Kediri for three years has not changed or remained for all types of promotional strategies and promotional tools used in promotional strategies but there is an increase through online media. IAIN Kediri has used appropriate promotional strategies as many as five types of promotional strategies and used a promotional mix strategy consisting of five main tools namely advertising, sales promotion, public relations and publicity, personal sales, direct marketing.(2). The lack of effective promotional strategies used by IAIN Kediri because over a period of three years due to one of them the intensity of the use of promotional tools in the promotion strategy is relatively fixed, as well as the absence of officers in the public relations department specifically established legally by the leaders of IAIN Kediri. this causes the IAIN Kediri institution to be able to achieve its objectives in marketing promotion strategies even though it is not yet fullyoptimal.